A pobre gente: as crônicas de João do Rio no jornal e no livro - Paulino, Fernanda Mansilia [UNESP] (2014)
The Gazeta de Notícias was an important discloser of the changes brought by the polemic urban reform of Rio de Janeiro in the turn of the 19th to the 20th century. Since the beginning, the newspaper showed itself favorable and optimistic about the measures of the Executive and Legislative Powers in favor of the modernization and ‘civilization’ of the city. In 1904, the chronicler Paulo Barreto, under the pseudonym of ‘João do Rio’, published, between the months of May and June, A pobre gente, a series of six long chronicles, in which he exposed, to the readers, the world of misery existing in the city of the belle-époque. In his chroniclereportage, João do Rio gave voice to the people that lived on the edge of society, establishing an interesting dialogue between his writings and the other headings of the Gazeta in which ‘the poor people’ was also the main character. In 1908, four of the six chronicles made public in the series passed from the newspaper to the book The Enchanting Soul of the Streets, and the analysis of this process highlights the importance of the relation between the text and the material characteristics of its media. Thus, we can conclude that the reportages of João do Rio dialogue with the discourse of the Gazeta about the poor people, reinforcing it. But, in a second moment, we will show a second level of relationship between the texts of João do Rio and the newspaper, considering the change of status of the reportages – that start being called chronicles when republished in the form of book –, through Gazeta’s own discourse about the book The Enchanting Soul of the Streets, composed by the later reportages published by that same newspaper. We will do it through the eyes of the critical fortune of João do Rio, of some texts by Barthes, Bakthin and Genette about the analysis of the narrative and its paratexts and, mainly, through the cultural history, and in this field, the writings of Roger ...